Detection of prodromal parkinson’s disease with fMRI data and deep neural network approaches - Shahriar, Farhan; Dey, Amarttya Prasad; Rahman, Naimur; Tasnim, Zarin; Tanvir, Mohammad Zubayer (Brac University, 2021)
Cataloged from PDF version of thesis.